2018
DOI: 10.1371/journal.pone.0194779
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of noise in multistable genetic circuits reveals ways to modulate heterogeneity

Abstract: Random fluctuations in the amount of cellular components like mRNA and protein molecules are inevitable due to the stochastic and discrete nature of biochemical reactions. If large enough, this so-called “cellular noise” can lead to random transitions between the expression states of a multistable genetic circuit. That way, heterogeneity within isogenic populations is created. Our aim is to understand which dynamical features of a simple autoregulatory system determine its intrinsic noise level, and how they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Diverse modelling approaches have proved useful to study stochastic switching in regulatory networks, ranging from the discrete chemical master equations and stochastic simulation algorithms to the continuous Fokker-Planck and Langevin equations. Those diverse tools and their refinements have been broadly used to study the interplay between noise properties and network topologies in shaping the steady-state bimodal distribution and transition rates associated with two phenotypic states 35 39 . In the present study, we use the joint framework of chemical Langevin equations 40 and bifurcation theory to address the interplay of stochasticity, transient adaptation and bistable switching.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse modelling approaches have proved useful to study stochastic switching in regulatory networks, ranging from the discrete chemical master equations and stochastic simulation algorithms to the continuous Fokker-Planck and Langevin equations. Those diverse tools and their refinements have been broadly used to study the interplay between noise properties and network topologies in shaping the steady-state bimodal distribution and transition rates associated with two phenotypic states 35 39 . In the present study, we use the joint framework of chemical Langevin equations 40 and bifurcation theory to address the interplay of stochasticity, transient adaptation and bistable switching.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic noise encompasses concepts such as developmental noise (Gavrilets and Hastings 1994), phenotypic hetero-geneity (Bódi et al 2017), cellular noise (Hortsch and Kremling 2018), biological noise (Eling et al 2019), intra-genotypic variability (Bruijning et al 2019), which take into account both intrinsic and extrinsic noises to varying degrees (Elowitz et al 2002). In quantitative genetics, phenotypic noise is historically known as environmental variance (or microenvironmental variability) (Falconer and Robertson 1956).…”
mentioning
confidence: 99%
“…Another limitation of our study is high interindividual variability in gene expression levels (high SD values) observed for many samples. While a relatively high level of molecular noise is common in gene expression studies [86,87], high interindividual variability in gene expression was particularly pronounced in genes that are involved in environmental responses in Arabidopsis thaliana [88]. This is an indication that harsh environmental conditions may be causing pronouncedly volatile gene expression levels on the interindividual, or possibly even intraindividual, levels on relatively short time scales, but this hypothesis warrants further studies.…”
Section: Discussionmentioning
confidence: 92%